PEMODELAN ANGKA KEMATIAN BAYI DENGAN PENDEKATAN GEOGRAPHICALLY WEIGHTED POISSON REGRESSION DI PROVINSI BALI - ELYNA, M ARRIE KUNILASARI; SRINADI, I GUSTI AYU MADE; SUSILAWATI, MADE (E-Jurnal Matematika; Volume 1, No 1, Tahun 2012DO - 10.24843/MTK.2012.v01.i01.p017, 2012)
Alpha In this study the used method of Geographically Weighted Poisson Regression (GWPR) is a statistical method to analyze the data to account for spatial factors. GWPR is a local form of Poisson regression with respect to the location of the assumption that the data is Poisson distributed. There are factors that are used in this study is the number of health facilities and midwives, the average length of breastfeeding, the percentage of deliveries performed by non-medical assistance, and the average length of schooling a woman is married. The research results showed that factors significantly influence the number of infant deaths in sluruh districts / municipalities in Bali is the average length of schooling a woman is married. Then the results of hypothesis test obtained the results that there was no difference who significant between the regression model poisson and GWPR in Bali.
Keywords: Poisson Regression, GWPR, Infant Mortality Rate (IMR)